AN ANALYSIS ON THE BACKGROUND OF ONLINE TRANSPORTATION CREW TO SUPPORT THE TOURISM AND NON-TOURISM ACTIVITIES (A Study on Online Transportation Drivers and Riders in Bandung) - Supriono Supriono (Profit: Jurnal Administrasi Bisnis, 2018)
Transportation becomes vital to tourism activities, especially when it comes to accessibility. Online transportation has become one of the choices for tourists to use in Bandung. This study focuses on analyzing how drivers or riders of online transportation in serving tourists and general consumers. The research method is qualitative with in-depth interviews with respondents (operators/drivers/riders) randomly chosen. Data Triangulation and Focus Group Discussion (FGD) are the methods use for data analysis. The results show that respondents join the online transportation, as the service has become such a trend in the city that more and more people are using it. Some takes the job as operators as their main job, while some others do that as simply a side job. Some even have a double membership status (both as offline and online transportation crew), yet some others choose to only become part of the online team. These riders or drivers purchase their vehicles by a credit system.Â Â